(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article examines the effectiveness of interactive technologies in teaching Computer Science Education. The study explores the role of multimedia tools, online learning platforms, virtual laboratories, and interactive teaching methods in improving students’ academic performance and motivation. Both qualitative and quantitative research methods were applied, including classroom observations, questionnaires, and interviews with teachers and students. The findings indicate that interactive technologies increase student engagement, enhance understanding of complex computer science concepts, and develop important skills such as problem-solving, critical thinking, and collaboration. The study also identifies several challenges related to technical resources and teacher preparedness. Overall, the research confirms that the integration of interactive technologies contributes significantly to the modernization and effectiveness of computer science education.